Karakteristik kimia, susut masak, dan tingkat kesukaan daging analog berbasis jamur shitake dengan tepung tempe - Valentinus Priyo Bintoro; Ashghar Yusuf Randika Islamay Putra; Siti Susanti (AGROINTEK, 2023)
Tempeh is a local potential to make meat analog as an alternative to common materials such as isolated soy protein and gluten. This study aims to determine the effect of adding tempeh flour on chemical characteristics, cooking loss, and preference level of shitake mushrooms-based meat analog and to determine the optimal formulation. The experiment was conducted using a Completely Randomized Design with the addition of tempe flour 0%, 10%, 20%, and 30% with 5 replications. Analytical procedures include protein content, fat content, cooking loss, preference level, and statistical analysis. The results showed that the addition of tempeh flour significantly affected the chemical characteristics, cooking loss, and preference level of taste, texture, color, and overall shitake mushrooms-based meat analog. The highest protein content was 22,79%, obtained by 30%, the highest fat content was 3,08%, obtained by 30%, and the lowest cooking loss was 2,54%, obtained by 30%. The highest preference for taste attributes was "like," obtained by 10%. The highest texture attribute was "like," obtained by 10%. The highest color attribute was "like," obtained by 30%, and the highest overall was "like," obtained by 10%. The increasing addition of tempeh flour caused an increase in chemical characteristics and preference level of the color attribute and caused a decrease in cooking loss and preference level of taste, texture, and overall. The optimal formulation is the addition of 30% tempeh flour which has produced analog meat with the quality closest to the standard, namely 23% protein, 3% fat, lowest cooking loss, and quite acceptable hedonic aspects.